Penerapan Smart Greenhouse Hidroponik Berbasis IoT Menggunakan EBT di Nurus Sunnah Farm - Vinda Setya Kartika; Achmad Fahrul Aji; Sri Kusumastuti; Raditya Artha Rochmanto; Sifa Nur Hidayat; Sadewa Alfansuri Putra (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
Public awareness of healthy lifestyles has increased the demand for fresh vegetables. However, limited land availability due to population growth poses a challenge for agricultural production. Hydroponics offers a solution without requiring large areas of land, yet its success depends heavily on controlling environmental parameters such as pH, temperature, and nutrients. This community service project aimed to implement smart greenhouse technology based on the Internet of Things (IoT) powered by renewable energy (RE) for curly lettuce cultivation at Nurus Sunnah Farm, Semarang City. The implementation stages included site surveys, system design and fabrication, installation, training, mentoring, and sustainability evaluation. The developed system utilized solar panels as an energy source and was equipped with three types of sensors (pH, TDS, temperature/humidity) integrated with ESP32 and an online monitoring platform. The results showed that the system was able to monitor and control hydroponic parameters in real time, with a pH sensor reading error of 0.0231 and a TDS sensor error of 0.0116. This innovation facilitates the management of nutrients, pH, and temperature, while reducing dependence on electricity from the national grid. The application of this technology has proven to enhance management efficiency, potentially maximize crop productivity, and support sustainable agriculture based on renewable energy